2021
DOI: 10.1097/md.0000000000025756
|View full text |Cite
|
Sign up to set email alerts
|

Uracil-tegafur vs fluorouracil as postoperative adjuvant chemotherapy in Stage II and III colon cancer

Abstract: We conducted a population-based cohort study enrolling patients with Stage II and III colon cancer receiving postoperative adjuvant chemotherapy with uracil and tegafur (UFT) or fluorouracil (5-FU) from the Taiwan National Health Insurance Research Database from 2000 to 2015. The outcomes of the current study were disease-free survival (DFS) and overall survival (OS). Hazard ratios (HRs) were calculated by multivariate Cox proportional hazard regression models. We compared our effectiveness results from the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Because of UFT’s tolerability and safety in an outpatient setting, it is the most commonly prescribed adjuvant chemotherapeutic for colon cancer in Taiwan [ 7 ]. A nationwide cohort study and meta-analysis demonstrated the similar effects of UFT and intravenous 5-FU on DFS and overall survival (OS), but UFT has a lower incidence of adverse events when used as a postoperative adjuvant chemotherapy in patients with locally advanced colon cancer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of UFT’s tolerability and safety in an outpatient setting, it is the most commonly prescribed adjuvant chemotherapeutic for colon cancer in Taiwan [ 7 ]. A nationwide cohort study and meta-analysis demonstrated the similar effects of UFT and intravenous 5-FU on DFS and overall survival (OS), but UFT has a lower incidence of adverse events when used as a postoperative adjuvant chemotherapy in patients with locally advanced colon cancer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%